Sensitive detection and measurement of oligogalacturonides in Arabidopsis - Pontiggia, Daniela; Ciarcianelli, Jacopo; Salvi, Gianni; Cervone, Felice; De Lorenzo, Giulia; Mattei, Benedetta (Frontiers in Plant Science, 2015)
Oligogalacturonides (OGs) are pectin fragments derived from the partial hydrolysis of the plant cell wall pectin; they are elicitors of various defense responses. While their activity is well documented, the detection of OGs produced in planta is still a challenging task. A protocol has been developed for the extraction and analysis of OGs from small samples of Arabidopsis tissues by using fluorescent labelled OGs, which allowed to monitor the efficiency of extraction. An efficient recovery was obtained by using a combination of calcium chelating agents at acidic pH. Off-line coupling of HPAEC with MALDI-TOF-MS or nanoESI-Orbitrap-MS/MS was used for the identification and characterization of oligosaccharides. The protocol was successfully applied to detect OGs by using low amounts (50 mg) of Arabidopsis leaves and very low amounts (30 mg) of senescent leaves. The protocol was also successfully used to detect OGs in Arabidopsis cell wall material digested with pectinases. The proposed extraction protocol followed by sensitive and high-resolution analysis methods allowed detection of OGs released from the cell wall in Arabidopsis tissues by using minimal sample material. The protocol may be useful to study OG-triggered plant immunity and cell wall remodeling during Arabidopsis growth and development.